2021
DOI: 10.3389/fimmu.2021.656414
|View full text |Cite
|
Sign up to set email alerts
|

Gut Leakage of Fungal‐Related Products: Turning Up the Heat for HIV Infection

Abstract: The intestinal epithelial layer serves as a physical and functional barrier between the microbiota in the lumen and immunologically active submucosa. Th17 T-cell function protects the gut epithelium from aggression from microbes and their by-products. Loss of barrier function has been associated with enhanced translocation of microbial products which act as endotoxins, leading to local and systemic immune activation. Whereas the inflammatory role of LPS produced by Gram-negative bacteria has been extensively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 75 publications
0
36
0
Order By: Relevance
“… 5 , 17 , 18 These findings suggest that BDG is originating from the gut. 16 Moreover, BDG levels were associated with inflammation markers, including proinflammatory cytokines, markers of myeloid cell activation, neopterin levels, and tryptophan metabolism in PLWH. 5 , 16 , 19 , 20 Although the association of BDG with gut damage and microbial translocation–associated inflammation were found by several studies in PLWH, the gut origin of these fungal products remain correlative.…”
Section: Microbial Translocation: When Fungi Join Force With Bacteriamentioning
confidence: 98%
See 2 more Smart Citations
“… 5 , 17 , 18 These findings suggest that BDG is originating from the gut. 16 Moreover, BDG levels were associated with inflammation markers, including proinflammatory cytokines, markers of myeloid cell activation, neopterin levels, and tryptophan metabolism in PLWH. 5 , 16 , 19 , 20 Although the association of BDG with gut damage and microbial translocation–associated inflammation were found by several studies in PLWH, the gut origin of these fungal products remain correlative.…”
Section: Microbial Translocation: When Fungi Join Force With Bacteriamentioning
confidence: 98%
“… 16 Moreover, BDG levels were associated with inflammation markers, including proinflammatory cytokines, markers of myeloid cell activation, neopterin levels, and tryptophan metabolism in PLWH. 5 , 16 , 19 , 20 Although the association of BDG with gut damage and microbial translocation–associated inflammation were found by several studies in PLWH, the gut origin of these fungal products remain correlative. Strategies used in animal models to confirm the gut origin of translocation LPS in SIV-infected macaques could be used in future studies.…”
Section: Microbial Translocation: When Fungi Join Force With Bacteriamentioning
confidence: 98%
See 1 more Smart Citation
“…Damage to the gastrointestinal epithelial gut barrier and subsequent translocation of microbes and their byproducts in the circulation constitute hallmarks of HIV infection and participate in systemic inflammation during chronic HIV infection [ 28 , 34 , 35 ]. The exact mechanisms responsible for gut damage and epithelial permeability are not fully understood, and these alterations do not improve upon ART initiation.…”
Section: CMV As a Perturbator Of Gut Barrier And Microbiota In People Living With Hiv (Plwh)mentioning
confidence: 99%
“…BDG is a component of the cell wall of fungi, and identification of plasma BDG is currently used for the clinical diagnosis of invasive fungal infections (124). Morris et al reported that high serum levels of BDG are associated with a decrease of CD4 + T-cell counts, a higher viral load, and activation of CD8 + T-cells in PLWH (125,126). Intestinal fatty acid binding protein (I-FABP), expressed in enterocytes, is released upon cell death, and enters into the systemic circulation (127).…”
Section: Hiv Infection Is Associated With Gut Microbiome Dysbiosis and Related Inflammationmentioning
confidence: 99%